Embedding a Blockchain Technology Pattern Into the QR Code for an Authentication Certificate - Aini, Qurotul; Rahardja, Untung; Tangkaw, Melani Rapina; Santoso, Nuke Puji Lestari; Khoirunisa, Alfiah (JOIN (Jurnal Online Informatika), 2020)
In the disruptive 4.0 era that emphasizes technological sophistication, blockchain is present as a technology that increasingly influences human life, helping humans in all aspects, including education. The role of blockchain technology in the world of education is to test the validity of diplomas, the increasing number of fake diplomas for an interest, both for work and continuing education to a higher level. The purpose of this research with the implementation of blockchain is expected to make it easier for users to verify the authenticity of a diploma. This study uses the SWOT analysis method to identify all possibilities that exist in blockchain technology. The final result of this research, the system will print a physical certificate in the form of paper in general, then the certificate will be printed a QR code. To verify numeric code on QR Code via scanning on smartphone or QR Reader. It is hoped that the blockchain technology applied to digital assets can reduce cases of forgery of diplomas and other important documents.